Democracy at work in Malaysia - Mohd Sani, Mohd Azizuddin; Ahmad Zakuan, Ummu Atiyah (UUM Press, 2017)
The prediction is that the 14th General Election (14thGE) is coming earlier than when it should be, as early as March 2017, instead of May 2018. On the one hand, with the DAP-led opposition in disarray for the last 18 months, since the departure of PAS, and on the other, the UMNO-led BN becoming more resolved and combative, the events leading to the forthcoming election promises more fireworks. The complexity of facts, fictions, perceptions and perspectives in making sense of the forthcoming 14thGE are intricate. “The present book, Democracy at Work, edited by Prof. Azizuddin and Dr. Ummu Atiyah of Universiti Utara Malaysia (UUM), provides an essential critical backdrop to build an informed understanding of what to expect from the 14thGE based on the 13 chapters of the book on the highly confusing but sometimes entertaining 13thGE. An added bonus is that the chapters are written not by the usual crop of opinionated ‘tired’ scholars but largely a fresh crop of serious and bright ones. The book is a must read for Malaysianists who enjoy talking, studying and making opinions on the ever complicated Malaysian politics, beyond the ambit of the mamak shops.” Shamsul A.B., Distinguished Professor and Founding Director, Institute of Ethnic Studies, (KITA) Universiti Kebangsaan Malaysia “A very essential book for those concerned with whether or not democracy is at work in Malaysia. It is indeed working.This major work explores some interesting issues dominated the public sphere during the GE13. Therefore, this book should be read by anyone interested about Malaysian politics and democracy.” Sivamurugan Pandian Professor at the School of Social Sciences, Universiti Sains Malaysia